Monolithic 3D CMOS Using Layered Semiconductors. Issue 13 (2nd February 2016) - Sachid, Angada B.; Tosun, Mahmut; Desai, Sujay B.; Hsu, Ching‐Yi; Lien, Der‐Hsien; Madhvapathy, Surabhi R.; Chen, Yu‐Ze; Hettick, Mark; Kang, Jeong Seuk; Zeng, Yuping; He, Jr‐Hau; Chang, Edward Yi; et al.
Abstract : Monolithic 3D integrated circuits using transition metal dichalcogenide materials and low‐temperature processing are reported. A variety of digital and analog circuits are implemented on two sequentially integrated layers of devices. Inverter circuit operation at an ultralow supply voltage of 150 mV is achieved, paving the way to high‐density, ultralow‐voltage, and ultralow‐power applications.